The relationship between intra- and intergenerational ecological justice: determinants of goal conflicts and synergies in sustainability policy - Stefanie Glotzbach; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
The guiding principle of sustainability is widely accepted in todays international policies. The principle contains two seperate objectives of justice with regard to the conservation and use of ecosystems and their services: (1) global justice between different people of the present generation (intragenerational justice); and (2) justice between people of different generations (intergenerational justice). Three hypotheses about the relationship between these objectives are logically possible and are, in fact, held in the political and scientific discourse on sustainable development: independency, facilitation and rivalry. Applying the method of qualitative content analysis we evaluate political documents and the scientific literature on sustainable development by systematically revealing the lines of reasoning and determinants underlying the different hypotheses. These determinants are the quantity and quality of ecosystem services, population development, substitutability of ecosystem services by humanmade goods and services, technological progress, institutions and political restrictions
Keywords: 330; Sustainable development; ecosystem services; intragenerational justice; intergenerational justice; ecological justice; sustainability research